2021
DOI: 10.1093/advances/nmaa161
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Selected Dietary Nutrient Intakes on Skeletal Muscle Insulin Sensitivity and Applications to Early Prevention of Type 2 Diabetes

Abstract: As the largest tissue in the body, skeletal muscle not only plays key roles in movement and glucose uptake and utilization but also mediates insulin sensitivity in the body by myokines. Insulin resistance in the skeletal muscle is a major feature of type 2 diabetes (T2D). A weakened response to insulin could lead to muscle mass loss and dysfunction. Increasing evidence in skeletal muscle cells, rodents, nonhuman primates, and humans has shown that restriction of caloric or protein intake positively mediates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…The calorie restriction intervention in this study improved blood insulin concentrations in both groups, reducing them by nearly 6% in the NS group and as much as 37% in the S group. Although the HOMA-IR index at gression of prediabetes to diabetes [52][53][54]. An improvement in insulin sensitivity was observed in healthy people with a short-term and very low-calorie diet, where caloric consumption was 500 kcal/day [55].…”
Section: Changes Following Calorie Restrictionmentioning
confidence: 99%
“…The calorie restriction intervention in this study improved blood insulin concentrations in both groups, reducing them by nearly 6% in the NS group and as much as 37% in the S group. Although the HOMA-IR index at gression of prediabetes to diabetes [52][53][54]. An improvement in insulin sensitivity was observed in healthy people with a short-term and very low-calorie diet, where caloric consumption was 500 kcal/day [55].…”
Section: Changes Following Calorie Restrictionmentioning
confidence: 99%
“…In addition, there is increasing evidence that some minerals, such as zinc and chromium, can protect people with diabetes from developing insulin resistance (Zhang et al, 2021). For women with diabetes, carbohydrate intake should be strictly controlled during pregnancy, and multivitamins or fruits and vegetables with antidiabetic effects, such as onions and bitter melon, should be ingested.…”
Section: Dietary Recommendations For Pregnant Women With Diabetesmentioning
confidence: 99%
“…In clinical trials, supplementation of VD has been shown to decrease the risk of diabetes and reduce the prevalence of diabetes in individuals without vitamin D deficiency by 10%–13% compared with the placebo treatment (Pittas et al., 2020). In addition, there is increasing evidence that some minerals, such as zinc and chromium, can protect people with diabetes from developing insulin resistance (Zhang et al., 2021). For women with diabetes, carbohydrate intake should be strictly controlled during pregnancy, and multivitamins or fruits and vegetables with antidiabetic effects, such as onions and bitter melon, should be ingested.…”
Section: Dietary Recommendations For Pregnant Women With Potential Risksmentioning
confidence: 99%
“…Dietary supplementation of isoleucine increased lipid accumulation and decreased the drip loss and shear force in the skeletal muscle of pigs ( Luo et al., 2018 , Table 1 ). Valine supplementation did not change lipid deposition in subcutaneous backfat and intramuscular fat tissues, however, valine metabolite 3-hydroxyisobutyrate (3-HIB) promoted fatty acid uptake and lipid accumulation in skeletal muscle by activating endothelial fatty acid transport ( Zhang et al., 2021b ). A high level of isoleucine supplementation (0.53% standardized ileal digestibility [SID] Ile) increased pH 24 h value and tended to decreased drip loss in longissimus dorsi muscle ( Xu et al., 2020 , Table 1 ).…”
Section: Dietary Supply Of Amino Acids Influences Lipid Deposition In...mentioning
confidence: 99%
“…Skeletal muscle, accounting to about 40% of the total body mass in adult mammals, not only performs normal body mechanical movements, but also plays an important role in regulating protein synthesis, energy metabolism, and glucose and lipid metabolic homeostasis via the interaction of myokines and the insulin signaling pathway, and the mechanism in turn underpins meat quality in farm animals (Rai and Demontis, 2016 ; Yang et al., 2019 ). In particular, some special nutrients and their supply status exert a critical role in regulation of skeletal muscle insulin sensitivity, energy metabolism and lipid accumulation, which has been well reviewed previously ( Zhang et al., 2021a , Zhang et al., 2021b ). In pig production, intramuscular fat content is a key factor influencing pork eating quality, such as taste and juiciness, while excess subcutaneous and visceral fat deposition will undermine the lean percentage and feed efficiency of finishing pigs.…”
Section: Introductionmentioning
confidence: 99%